Bioequivalence study of two oral lincomycin formulations (lincopharm 800® and lincoyosr®) in broiler chickens - Elkomy, Ashraf; Aboubakr, Mohamed (International Journal of Pharmacology and Toxicology, 2020)
The present study was designed to assess the comparative bio-equivalence of Lincopharm 800® and Lincoyosr® in healthy broiler chicken after oral administration of both products in a dose of 20 mg lincomycin base/kg b.wt. Twenty four broiler chickens were divided into two groups. The first group was designed to study the pharmacokinetics of Lincopharm 800®, while the 2nd group was designed to study the pharmacokinetics of Lincoyosr®. Each broiler chicken in both groups was orally administered with 20 mg lincomycin base/kg b.wt. Blood samples were obtained from the wing vein and collected immediately before and at 0.08, 0.16, 0.25, 0.5, 1, 2, 4, 8, 12 and 24 hours after a single oral administration. The disposition kinetics of Lincopharm 800® and Lincoyosr® following oral administration of 20 mg lincomycin base /kg b.wt, revealed that the maximum blood concentration of lincomycin [Cmax] were 4.81 and 4.62 μg/ml and attained at [tmax] of 1.36 and 1.35 hours, respectively. In conclusion: Lincoyosr® is bioequivalent to Lincopharm 800® since the ratios of Cmax, AUC0-24 and AUC0-∞ (T/R) was 0.96, 0.92 and 0.91 respectively. These are within the bioequivalence acceptance range. Lincoyosr® and Lincopharm 800® are therefore bioequivalent and interchangeable.